A tree-based decision method for the configuration design of reconfigurable machine tools. (October 2018) - Wang, Guoxin; Shang, Xiwen; Yan, Yan; Allen, Janet K.; Mistree, Farrokh
Highlights: A common model to describe a reconfigurable machine tool using a tree structure is presented. Feasible configurations of reconfigurable machine tools are generated using an analysis of capability and functionality. A satisfactory configuration of a reconfigurable machine tool is based on the trade-off between cost and reconfigurability. The proposed method is applied to three production scenarios which involve a dynamic design process for RMT reconfiguration. Abstract: A reconfigurable machine tool (RMT) can repeatedly be configured to respond to a wide range of requirements (such as a change in function or capacity) in a cost-effective manner. One of the challenges in RMT reconfiguration is the high complexity of the modular configuration due to customization. Furthermore, the possible design space may be enormous as the number of modules increases. Hence, an effective way to describe the diverse configurations of an RMT and evaluate its performance is needed. In this paper, we propose a tree-based method to determine the configuration design for reconfiguration of an RMT. The method includes: 1) defining a computational common model for a reconfigurable machine tool configuration using a tree structure, 2) identifying concepts that combine the desired function and capability, and 3) determining those concepts which satisfy two goals: minimizing cost and maximizing reconfigurability. The proposed method is illustrated by designing an RMT for a transmission box for three different production scenarios: the RMT initial operation, a change in operational features and a change in operational quantity. The benefit of using the proposed method is its improved functionality.